The Communication Strategy Used By Japanese Learner at the Basic Level - Dyah Prasetiani; Lispridona Diner (Intelektual Pustaka Media Utama, 2018)
Students at the basic level in Department Education Japanese of Semarang State University have difficulties in Japanese speaking. They could not produce oral Japanese smoothly. Sometimes they said couple words in Bahasa Indonesia to express their ideas. In communication strategy there is a systematic technique used by foreign language learners to express their ideas when faced with the difficulty of communicating because of the limitations of second language mastery. The findings are the learners already have passed the stage of mastery of simple-level linguistic rules, so they have a tendency to pursue in various ways to make their message acceptable. The characteristic of communication strategy they used are directly translated an utterance literally in the concept of their mother tongue, and use those terminology in their mother tongue and English in Japanese utterance. The reasons that influence the use of these communication strategies are that students' grammar and vocabulary skills are insufficient to communicate in various fields as they are still in the early learning stages.